CHK1 inhibition exacerbates replication stress induced by IGF blockade - Wu, Xiaoning; Seraia, Elena; Hatch, Stephanie B.; Wan, Xiao; Ebner, Daniel V.; Aroldi, Francesca; Jiang, Yanyan; Ryan, Anderson J.; Bogenrieder, Thomas; Weyer-Czernilofsky, Ulrike; Rieunier, Guillaume; Macaulay, Valentine M. (Oncogene, 2022)
We recently reported that genetic or pharmacological inhibition of insulin-like growth factor receptor (IGF-1R) slows DNA replication and induces replication stress by downregulating the regulatory subunit RRM2 of ribonucleotide reductase, perturbing deoxynucleotide triphosphate (dNTP) supply. Aiming to exploit this effect in therapy we performed a compound screen in five breast cancer cell lines with IGF neutralising antibody xentuzumab. Inhibitor of checkpoint kinase CHK1 was identified as a top screen hit. Co-inhibition of IGF and CHK1 caused synergistic suppression of cell viability, cell survival and tumour growth in 2D cell culture, 3D spheroid cultures and in vivo. Investigating the mechanism of synthetic lethality, we reveal that CHK1 inhibition in IGF-1R depleted or inhibited cells further downregulated RRM2, reduced dNTP supply and profoundly delayed replication fork progression. These effects resulted in significant accumulation of unreplicated single-stranded DNA and increased cell death, indicative of replication catastrophe. Similar phenotypes were induced by IGF:WEE1 co-inhibition, also via exacerbation of RRM2 downregulation. Exogenous RRM2 expression rescued hallmarks of replication stress induced by co-inhibiting IGF with CHK1 or WEE1, identifying RRM2 as a critical target of the functional IGF:CHK1 and IGF:WEE1 interactions. These data identify novel therapeutic vulnerabilities and may inform future trials of IGF inhibitory drugs.